STATUS AND PROSPECTS OF DEVELOPMENT OF INSURANCE COVERAGE ORGANIZATIONS BUSINESS INFRASTRUCTURE OF REAL ESTATE MARKET - A. N. Jampol'skij (Модернизация, инновация, развитие, 2015)
This paper presents an analysis of the current state of the Russian market of insurance services provided by appraisers and notaries working in the real estate market. According to the results of analysis of the real estate market infrastructure organizations highlighted the company business and intermediary market infrastructure. It is possible to identify the specifi c risks and to compare them to exist in the Russian insurance. Liability insurance organizations – representatives of the business infrastructure of the real estate market serves to increase the economic security of transactions, and in this context deserves regular monitoring for the purpose of correction of legislation in relation to modern economic realities. The paper presents an analysis of the legislation governing the liability insurance of notaries and appraisers, recommendations are made to improve the practice of insurance.